Group Threat, Same-Sex Marriage, and Hate Crime Based on Sexual Orientation. (7th June 2022) - Piatkowska, Sylwia J.; Messner, Steven F.
Abstract: Prior research has begun the task of assessing the applicability of group threat theory to explain sexual orientation hate crime. Drawing upon this perspective, researchers have hypothesized that relatively large and growing gay populations might be perceived as a threat to heterosexual norms, leading to sexual orientation hate crimes. Previous work has also identified an additional source of threat that may be particularly salient: threat to traditional marriage. Using data for a sample of metropolitan areas, we assess the impact of a previously unexamined potential source of threat: same-sex marriage. We also compare the relationships between the relative size and growth of the gay population and hate crimes expressed as incidence and victimization rates. The results reveal that the effects of the gay population's relative size on incidence vs. victimization rates differ in important respects, and that the level of same-sex marriage is positively associated with both hate crime rates.